Laparoscopic artificial insemination in small ruminants: technological integration, economic evaluation, and future perspectives - Kang, Ting-Chieh; Lai, I-Ling; Shen, Perng-Chih (Frontiers in Veterinary Science, 2025)
Laparoscopic artificial insemination (LAI) has emerged as a cornerstone technology for genetic improvement in small ruminants. By directly depositing semen into the uterine horns through minimally invasive surgery, LAI effectively bypasses the cervical anatomical barrier that hinders transcervical insemination. This approach has elevated pregnancy rates with frozen–thawed semen from 20 to 40% using conventional methods to 60–70%, establishing LAI as the “gold standard” in small ruminant reproduction. This review develops an integrated framework centered on LAI, systematically highlighting how emerging technologies directly enhance its precision and automation. Artificial intelligence–driven multivariate prediction models now enable pregnancy rate forecasting (AUC = 0.86), while computer vision technologies provide highly accurate estrus detection (98.56% accuracy), optimizing insemination timing. Robotic-assisted systems further refine surgical precision, and the integration of Internet of Things (IoT) and digital twin platforms enables end-to-end intelligent reproductive management. Economic evaluations indicate that LAI delivers significant returns on investment when the genetic value of disseminated germplasm is sufficiently high. Although technical complexity and equipment costs remain challenges, the integration of LAI with emerging technologies is driving a paradigm shift toward precision and intelligent management in the small ruminant industry, offering critical support for global food security and sustainable development.